VD_FINDINFO Jug / 2012 / 94 vom 24. Mai 2012 - VD Tribunal cantonal (2012)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 al. 1 CC, 22 al. 1 LFLP, 24a LFLP, 7 OLP, 8a al. 1 OLP, 12 OPP2, 111 al. 2 LPA-VD